COVID-19 and Indian frontline workers - Chaudhary, Ankit; ., Priyanka; Chamotra, Shaina (International Journal of Research in Medical Sciences, 2021)
The pandemic of COVID-19 has posed challenges and revealed so many shortcomings in vision and execution of health system. Despite of threats, it has also given ample opportunities for improvement in health care delivery. Health professional of each category has contributed beyond their capability in curbing the pandemic. Frontline workers like health workers and accredited social health activist (ASHA) workers have worked at the grass root level and given their absolute best despite their already stringent work schedule and job profile. Already trusted with so many health programs and community activities, they have excelled in management of the pandemic. However, this has posed a serious question and threat to already burdened health system. The pandemic has further worsened already compromised plight of frontline health personnel. It is high time that appropriate consideration be given to such workers in order to improve health system. Some form of appreciation in terms of monetary benefits, some administrative commendation or welfare measures must be thought to recognize their sincere efforts.